Effect of corn stigma extract on physical and antioxidant properties of biodegradable and edible gelatin and corn starch films - Boeira, Caroline Pagnossim; Flores, Déborah Cristina Barcelos; Alves, Jamila dos Santos; Moura, Márcia Regina de [UNESP]; Melo, Pamela Thais Sousa [UNESP]; Rolim, Clarice Madalena Bueno; Nogueira-Librelotto, Daniele Rubert; Rosa, Claudia Severo da (Elsevier, 2022)
The development of bio-based food packaging with antioxidant properties is an important research topic and has gained prominence these days. In this study, bioactive films were developed based gelatin-corn starch (GCS) incorporated with corn stigma extract (CSE) at different concentrations (15% and 25%; w/v). In preliminary tests, the extract maintained cell viability above 90% indicating that it is safe for application as an active ingredient. Insertion of the extract did not influence the thickness of the films but caused a slight change in optical properties. Scanning electron microscopy (SEM) analysis revealed interactions between the extract's bioactive compounds with gelatin and corn starch compounds, which may have improved the mechanical properties (elongation at break, Young's modulus). The addition of 25% corn stigma extract increased the contact angle, giving the film a hydrophobic character. Furthermore, at this concentration, a 15% reduction in water vapor permeability was observed. The elaborated films showed complete biodegradability before the tenth day of the study. It can be inferred that the films with corn stigma extract have good antioxidant properties, indicating that they can be used as an ingredient for food packaging.
Keywords: Antioxidant packaging; Biodegradable packaging; Reuse of agricultural waste